Cross‐reactivity between tick and wasp venom can contribute to frequent wasp sensitization in patients with the α‐Gal syndrome. Issue 1 (17th January 2022) - Kiewiet, Mensiena B. G.; Perusko, Marija; Grundström, Jeanette; Hamsten, Carl; Starkhammar, Maria; Apostolovic, Danijela; van Hage, Marianne
Abstract: Background: α‐Gal syndrome (AGS) is a food allergy with severe delayed allergic reactions, mediated by IgE‐reactivity to galactose‐α1, 3‐galactose (α‐Gal). AGS is strongly associated with tick bites. An increased incidence of venom sensitization has been found in AGS patients. Here, we evaluated the frequency of wasp sensitization in Swedish AGS patients and the possible cross‐reactivity between wasp venom and tick proteins. Methods: Sera from 136 Swedish AGS patients and 29 wasp‐positive non‐AGS control sera were analyzed for IgE‐reactivity against wasp venom ( Vespula spp.), the European tick Ixodes ricinus (Streptavidin ImmunoCAP), α‐Gal and total IgE by ImmunoCAP. The presence of α‐Gal on wasp venom proteins ( Vespula vulgaris ) was investigated by western blot (WB), and possible cross‐reactivity between wasp venom and tick proteins by enzyme‐linked immunosorbent assay and WB. Involvement of cross‐reactive carbohydrate domains (CCDs) was also assessed. Results: Wasp sensitization was present in 54% of AGS patients, although the IgE levels were low. Wasp sensitized patients had higher IgE levels to α‐Gal and total IgE levels compared to non‐wasp sensitized AGS patients. α‐Gal was not detected in wasp venom, but cross‐reactivity between wasp and tick proteins was demonstrated which was not dependent on CCDs. The same cross‐reactivity was also observed in the control sera. Furthermore, 17 putative cross‐reactive peptides were identified using an in silico approach. Conclusions: For the first time, cross‐reactivity between wasp venom and tick proteins has been described. This may be a reason why the majority of Swedish AGS patients, who have all been tick bitten, are also sensitized against wasp.